Preparation of the Future Mentors for Usage of the Elements of National Mathematics Working with Children of Preschool Age - Anna Kit; Iryna Gryndii (Pedagogical Discourse, 2012)
Preparation of the future mentors for usage of the elements of national mathematics, familiarization with national units of measurement, formation of mathematical concepts by means of folklore (folk riddles, proverbs, sayings) working with children of preschool age are studied in this article.